Flunisolide Decreases Exhaled Nitric Oxide and Nitrotyrosine Levels in Asthmatic Children - A. Bodini; D. G. Peroni; F. Zardini; M. Corradi; R. Alinovi; A. L. Boner; G. L. Piacentini (Mediators of Inflammation)
Background. Exhaled nitric oxide (FeNO) has been reported to be elevated in the oxidative stress involved in asthmatic patients, and the reaction of nitric oxide (NO) with superoxide anions results in the formation of nitrotyrosine. The purpose of this study was to investigate the effect of inhaled steroid treatment on nitrotyrosine levels collected by exhaled breath condensate (EBC) and on FeNO. Methods. This was a single-blind placebo-controlled study. The lung function, FeNO, and nitrotyrosine levels were evaluated in 10 asthmatic children. Results. The nitrotyrosine levels were stable during the placebo period (T0 = 1.16 ng/ml versus T1 = 1.05 ng/ml; NS.), whereas they decreased after the treatment with flunisolide (T2 = 1.14 ng/ml versus T3 = 0.88 ng/ml; P<.001). No significant reduction in FeNO levels was observed after placebo treatment (T0 = 38.4 ppb versus T1 = 34.7 ppb, NS.). In contrast, FeNO values decreased significantly being at T3 = 14.9 ppb (T1 versus T3; P=.024). Conclusions. This study shows that corticosteroid treatment reduces nitrotyrosine levels in EBC of asthmatic subjects.